The reproduction of heritage in a Chinese village: whose heritage, whose pasts?. Issue 3 (15th March 2016) - Zhang, Yingchun; Wu, Zongjie
Abstract: The study investigates heritage practices in a Chinese village, by describing the tensions that have played out among different voices, meanings and understandings centred on the village's heritage. In the process of 'heritageisation', stakeholders that include the state, the local government, the villagers and the principal lineage strive to negotiate different cultural meanings, values and the traditions. Consequently, three different heritage discourses coexist alongside each other in one locality. On the one hand, the 'authorised heritage discourse' is taken up by the government to weave and frame a narrative of nation-building around a Memorial Park. On the other hand, the village uses the past to foster local identity of the place in an attempt to attract tourists. For its part, the major lineage in the village uses the ancestral hall to continue the long tradition of remembering their ancestors via worshiping ceremonies. In between are a medley of heritage sites and artefacts existing in a state of flux and struggle over their conservation. The authors contend that, no matter how mundane, grand or hybrid, assemblages of rich and locally meaningful heritage, such as depicted in this article, should be cherished and utilised for the present agenda of cultural construction in rural China.